2014
DOI: 10.1089/hum.2013.132
|View full text |Cite
|
Sign up to set email alerts
|

SERCA2a Gene Therapy Can Improve Symptomatic Heart Failure in δ-Sarcoglycan-Deficient Animals

Abstract: The loss of dystrophin or its associated proteins results in the development of muscle wasting frequently associated with cardiomyopathy. Contractile cardiac tissue is injured and replaced by fibrous tissue or fatty infiltrates, leading to a progressive decrease of the contractile force and finally to end-stage heart failure. At the time symptoms appear, restoration of a functional allele of the causative gene might not be sufficient to prevent disease progression. Alterations in Ca 2 + transport and intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…This is consistent with the results of previous study (Zarain-Herzberg et al, 2012) that suggested that decreased SERCA2a activity may have a direct relationship with cardiac dysfunction and cardiomyocyte enlargement (Fernandes et al, 2015). Consequently, SERCA2a is now regarded as a novel gene target for HF therapy in the clinic (Bouyon et al, 2014;Chen et al, 2019). Surprisingly, VA treatment could significantly restore SERCA2a mRNA and protein expression levels, thereby also restoring SERCA2a activity and expression.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of previous study (Zarain-Herzberg et al, 2012) that suggested that decreased SERCA2a activity may have a direct relationship with cardiac dysfunction and cardiomyocyte enlargement (Fernandes et al, 2015). Consequently, SERCA2a is now regarded as a novel gene target for HF therapy in the clinic (Bouyon et al, 2014;Chen et al, 2019). Surprisingly, VA treatment could significantly restore SERCA2a mRNA and protein expression levels, thereby also restoring SERCA2a activity and expression.…”
Section: Discussionsupporting
confidence: 91%
“…SERCA2a holds a key role in the development and progression of heart failure, so after the initial work by Schwartz and coworkers, it was rather obvious to test its therapeutic potential [38][39][40]. Briefly, we could demonstrate that from a therapeutic perspective at a clinical stage of patent heart failure, great benefits could be obtained by targeting cardiomyocyte Ca 2+ homeostasis through SERCA2a gene expression than rescuing the initial causative genetic defect [41]. These findings as well as results from several other labs strongly support the strategy of cardiac gene therapy for heart failure based on restoring appropriate Ca 2+ handling [42][43][44].…”
Section: Heart Failurementioning
confidence: 99%
“…112,116 AAV-mediated SERCA expression has also improved cardiac function in various canine models of heart failure. 117,118 Based on these results, it is possible that AAV SERCA therapy may also reduce muscle disease in cDMD dogs.…”
Section: Dystrophin-independent Gene Therapy In the Cdmd Modelmentioning
confidence: 99%